Changing rainfall patterns and farmers ’ adaptation through soil water management practices in semi- arid eastern Kenya - Recha, John W.M.; Mati, Bancy M.; Nyasimi, Mary; Kimeli, Philip; Kinyangi, James; Radeny, Maren A.O. (Informa UK Limited, 2016)
There is limited documentation of soil and water management technologies that enhance adaptation to climate change in drylands of Kenya. Rainfall patterns were analyzed in the semi-arid Machakos and Makueni counties of eastern Kenya using historical data. A total of forty-three smallholder farmers implementing soil water management practices were sampled, and an estimate of the seasonal water budget for current crop and livestock production systems computed. Analysis of rainfall amounts and distribution shows increasing variability, with the average annual total amounts decreasing over the past 50 years. Furthermore, the number of rainy days within the March-April-May season that can support crop growth is gradually decreasing. These decreases are however not significant at P <0.05. There were more seasons with low rainfall amounts compared to those with high rainfall amounts. All these subject the smallholder crop and livestock production system to limited soil moisture. Farmers address the risk by harnessing and utilizing green (rainfall stored in soil) and blue (rainfall collected into storage tanks) water technologies. The study found that farmers in these semi-arid counties practice fifteen diverse soil and water management interventions on their farms. The most popular practices are cut-off drains, retention ditches, terracing, run-off harvesting, and agroforestry. The estimated seasonal water budget indicates the need for integrated soil and water management interventions to address the crop and livestock production constraints.